The Influence Of Brand Image, Brand Awareness, and Brand Trust On Purchase Decisions Amidst The Boycott Issue: A Case Study of Starbucks in Surabaya - Alfian Dwi Ramadhan; Ugy Soebiantoro (International Journal of Economics, Commerce, and Management, 2025)
The phenomenon of image degradation due to global boycott issues, including the Boycott, Divestment, and Sanctions (BDS) movement, has influenced consumer behavior, especially towards international brands such as Starbucks. This occurrence serves as the basis for the study's analysis of how Surabaya consumers' decisions to buy Starbucks are influenced by brand image, brand awareness, and brand trust. 112 Starbucks customers in Surabaya participated in a survey as part of this study's quantitative methodology. ThWith the use of SmartPLS 3.0 software, the data analysis method employed is Partial Least Squares Structural Equation Modeling (PLS-SEM).  The study's findings show that purchase decisions are positively and significantly impacted by brand image, brand awareness, and brand trust. This finding indicates that these three variables have an important role in encouraging consumers to continue making purchases, even amidst reputational pressure due to social issues. This study provides implications for company marketing strategies in maintaining and building brand elements that can strengthen consumer loyalty and purchasing decisions. The study's findings show that purchase decisions are positively and significantly impacted by brand image, brand awareness, and brand trust. This finding indicates that these three variables have an important role in encouraging consumers to continue making purchases, even amidst reputational pressure due to social issues. Specifically, brand image is found to enhance consumers' emotional connection with the brand, which can mitigate the negative impacts of global boycotts or negative publicity. Brand awareness is shown to increase familiarity and recognition, which in turn solidifies consumer trust and loyalty. Lastly, brand trust has the strongest direct effect on purchase intentions, demonstrating that consumers are more likely to remain loyal to a brand they trust, even in the face of external challenges.